Is there any way out? Black Mirror as a critical dystopia of the society of the spectacle - Lopes, Juliana (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
One of the most appalling (and appealing) aspects of Black Mirror is the atmosphere of complete hopelessness in which the majority of episodes end. This essay, however, tries to prove that, at least in Nosedive, there is a way out. Using the concepts of (canonical) dystopia and critical dystopia, as understood by Rafaela Baccolini and Tom Moylan, along with Guy Debord’s idea of the society of the spectacle, I will provide a theoretical apparatus to support my analysis of the episode. After identifying the main aspects which cause and perpetuate the dystopic state on the episode, the paper will also explore their effects on people. Having this context in mind, the essay focuses on the importance of performances and social masks as one of the main results of a dystopia of the society of the spectacle. Then, it analyzes the role of different characters who somehow manage to escape the dystopic order and, simultaneously, reflects on the intriguing ending that only seems to reinforce the possibility to face Nosedive as a canonical dystopia. In conclusion, this essay argues that the non-obvious ways out of that dystopian state have actually a bigger impact on the audience.